ANALISIS KEMUDAHAN PENGGUNAAN DAN PERSEPSI RISIKO TERHADAP MINAT MENGGUNAKAN SHOPEE PAYLATER (STUDI KASUS PADA MAHASISWA POLITEKNIK NEGERI BALI) - SAFITRI, ADELIA; GEDE, I GUSTI KETUT; SUPIATNI, NI NYOMAN (GANEC SWARA, 2024)
In today's digital era, technology has advanced rapidly, enabling people to use their phones for various purposes easily, quickly, and instantly. E-commerce has grown rapidly in Indonesia, with Shopee being a leading platform. Shopee PayLater (SPayLater) allows users to make purchases with payment deferred to a later date. This study aims to analyze the factors of user-friendliness and risk perception influencing the interest of Bali State Polytechnic students in using SPayLater. Based on a survey conducted, SPayLater is very popular among students due to its convenience and various promotions offered. However, risk perceptions such as concerns about personal data and financial risks also influence user decisions. This research is quantitative, using data collected from 100 respondents who met the criteria through questionnaires. The method employed is multiple linear regression analysis using SPSS. The results show that userfriendliness and risk perception have a positive and significant impact on the interest in using SPayLater. High user-friendliness increases consumer interest, while risk perception does not reduce it. Both variables simultaneously influence consumer interest in using SPayLater. This study is expected to contribute to both companies and users.